Relation cellular- molecular between serum IL10 levels and hyperalgesia variation in adjuvant- induced arthritis - Zenab Akhtari; Jalal Zaringhalam; Akram Eidi; seyd Ali HaeriRuhani; Homa Manaheji; Elahe Tekieh (Iranian South Medical Journal, 2015)
Background: Regarding to the important anti-inflammatory role of IL10 during inflammation process and hyperalgesia and edema variation during CFA-induced arthritis and also the increase of Spinal mu opioid receptor (mOR) expression, in this study researchers investigate the role of serum IL10 level on mOR expression and edema and hyperalgesia variation during different stages of Complete Freund`s Adjuvant (CFA) - induced arthritis in male Wistar rats.